Perlindungan Hukum Terhadap Kreditur Atas Jaminan Hutang Berupa Hak Cipta Konten Youtube - Elvira Lorna Fidelia Zai; Theresia Nolda Agnes Narwadan; Muchtar Anshary Hamid Labetubun (PATTIMURA Law Study Review, 2023)
ABSTRACT: In Government Regulation Number 24 of 2022 Concerning the Creative Economy, it makes it easy for creative economy actors who have intellectual property rights certificates through this regulation, the Government gives permission to content creators who already have intellectual property certificates to serve as bank credit guarantees. However, there are still confusions in this implementation because the creditor will suffer losses when the debtor's default occurs because the collateralized asset is blocked. so that the valuation of assets in the form of intellectual property rights on the youtube channel is very difficult to do based on Article 25 paragraph 1c Law 24/1999 concerning fiduciary guarantees stipulating that fiduciary guarantees are deleted due to the destruction of objects that are objects of fiduciary guarantees automatically bank financial institutions suffer losses. The research method used is normative juridical, using a problem approach, namely the statutory approach and contextual approach, the sources of legal materials used are primary, secondary and tertiary legal materials. The legal material collection technique used was library legal material collection, which was analyzed using qualitative methods. The results of this study indicate that legal protection for creditors for copyrighted YouTube content is in the form of copyright, namely through preventive legal protection provided by the government in the form of prevention before violations occur, efforts are made to prevent violations from occurring, namely the application of judgment on banks to carry out the precautionary principle when giving credit to customers by conducting judgments on private customers, businesses and collateral objects provided by customers and repressive protection, namely final protection in the form of sanctions and punishments carried out through executorial titles. Settlement of disputes with YouTube content copyright as collateral is litigation settlement by filing lawsuits with commercial courts and non-litigation with settlements through negotiation, mediation and conciliation.